Structured doctoral programmes for developing the scholar and the scholarship: Lessons from practice - Wilmot, Kirstin (Critical Studies in Teaching and Learning, 2024)
There are growing international calls for doctoral education to embrace more collaborative, structured supervision models. While the uptake of such models has been slow in South Africa, interesting forms of structured models are emerging. This study critically reflects on one such example, highlighting the successes and challenges to provide the field with practical insights of how such a model can be conceptualised. Focusing on a curriculated PhD project in the field of higher education studies, the paper explores the extent to which the project enhanced the development of the scholarship and scholarly dispositions in candidates. Inductive thematic analysis of interviews with 12 doctoral candidates was used in the first phase of analysis to reveal the salient issues in the data. The second phase of analysis drew on Legitimation Code Theory’s dimension of Specialization to understand the different kinds of learning afforded by the programme. The findings show how the curriculated programme provided an important bridge into disciplinary knowledge, and it reveals how the collaborative community played a critical role in strengthening students’ theoretical and disciplinary knowledge as well as cultivating key scholarly dispositions such as criticality, voice, and collaboration.